ANALISIS KUALITAS PELAYANAN DI RESTORAN KELONG BABA KOTA BATAM - Batti, Marlow Shane; Dailami, Dailami; Thamdzir, Moh; Ilham, Wahyudi; Sukmamedian, Haufi (Puslitabmas Batam Tourism Polytecnic, 2024)
A restaurant is a business in the food service industry or part of a tourist accommodation business whose role is to meet the needs of tourists or customers. In this case, good service quality really determines the development of restaurants outside of food and drink. Free. Kelong Baba Batam Restaurant is a restaurant that provides quality service. This research aims to see the application of service quality and what improvements can be made in the management of the Kelong Baba Batam Restaurant, so that the quality of the restaurant's service can be improved or reduced. This research will be carried out using a qualitative descriptive approach. Kelong Baba Restaurant itself has a modern concept and has an attractive interior that makes guests comfortable eating there. Not only is the interior attractive, Kelong Baba Restaurant is also very sensitive to what guests need to make the guests themselves comfortable.